ORGANIZING EFFECTIVE INTERACTION WITH REMOTE PERSONNEL AS A FACTOR OF ECONOMIC RATIONALITY - Zholdoyakova Gulden Edylovna; Kasimbekova Meiramkul Aldashevna; Utarbaeva Gulnara Kydyrgalievna; Satkalieva Tamara Sagimbaevna; Nurgalieva Zhanna Ergalievna (Academic Journal of Physical and Chemical Sciences, 2020)
The modern labor market is rapidly changing. Today, software integrated with each other, understandable for the average user with advanced communication capabilities, management and control functions, is in high demand. Routine tasks are being automated at all levels of management, and the influence of information technology and artificial intelligence development trends on all areas of the business and its participants is becoming global. Remote employment in a pandemic is relevant and represents a work process carried out outside the traditional place of work and involving interaction with the employer through telecommunication and information technologies. Both the employer and the employee have advantages and disadvantages in the application and use of remote work. How effective it is in this particular case, it is up to each employer to decide on the direction of the organization, the category of personnel and the goals facing the company. The authors proposed ways of effective interaction with remote personnel.